CULTURAL HERITAGE DIGITIZATION OF BOROBUDUR AREA TOURISM: A PROJECT-BASED LEARNING - Barus, Irma Rasita Gloria; Fami, Amata; Rahayu, Kania Sofiantina (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2023)
In supporting the efforts to preserve the nation’s cultural heritage, this research aimed to implement project-based learning by designing e-books as digital information media to promote tourism development. This research attempted to report and illustrate the implementation of project-based learning, which aimed to explore twenty potential tourist attractions in the surrounding villages of the Borobudur Temple in Central Java, Indonesia. This research involved 127 students of the Informatics Management Study Program enrolled in the Graphic Design course. This qualitative case study exemplified the implementation of project-based learning in designing and digitizing information media in the form of a collection of e-books. The overall process consisted of three main stages, i.e., pre-production, production, and post-production. The stages included conducting preliminary research; formulating the concept of design; collecting visual and typographic references; outlining; performing the design and digitization; and presenting the final product. The data were taken from class observations and documentation from March to June 2022. By demonstrating the project-based learning model of preserving the cultural potential of twenty traditional villages surrounding the Borobudur Temple area in a digital environment, it is hoped that the digitized cultural heritage can be introduced to and recognized by wider audiences.